Spatial distribution of coseismic mass movements by 2015 Gorkha Earthquake in six districts of Central Nepal - M.R. Dhital; M.L. Rijal; S.R. Bajracharya (Lowland Technology International, 2016)
The Mw 7.8 Gorkha earthquake of 25 April 2015 and its many severe aftershocks generated about 4000 landslips. We have carried out field investigation of mass movements in the most severely-affected six districts of Central Nepal. The study revealed that the size and distribution of slides is strongly controlled by their position on landscape. An overwhelming majority of them was less than 5 m deep. Many slides were found to originate near a long and high crest or a peak. The slopes that had the highest internal relief suffered the most from the seismically-triggered failures. On the other hand, the old and large failures that were confined mainly to the river valleys were rather insensitive to earthquake shaking.